STATUS SOSIAL-EKONOMI DAN KADAR HORMON TIROTROPIN RUMAH-TANGGA PENGGUNA GARAM BERIDOIUM DI PERKOTAAN INDONESIA: ANALISIS DATA RISKESDAS 2007 - Djoko Kartono; Whinie Lestari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
ABSTRACT Iodized salt is the long term and sustainable strategy to improve iodine intakeof the community.Level of thyroid stimulating hormone (thyrotropin hormone) can be used as indicator of iodine intake adequacy. To study the socio-economic status of households using iodized salt and thyrotropin hormone level in urban areas. Riskesdas data 2007 that include 280.000 households was used.Thyrotropin hormone data include 9.457 people aged above 1 years. Variables included classification of village, rapid test on salt, education and occupation of households’ head, household expenditure and level of thyrotropin hormone. Around 80 percentof households where households’ head graduated from college/university used salt containing sufficient iodine. Only 18 percent households with households’ headworks as government workers used salt containing sufficient iodine. Around 70 percent households in 5th quintile of household’s expenditure were using salt with sufficient iodine content. Around 70 percent households in urban areas were using salt withsufficient iodine content.Among children 1-4 years, percentage of low category of thyrotropin hormon level was 3.3 percentand among 60 years of age and above was 15.8 percent. The higher the educational levelthe higher the percentage of households used salt with sufficient iodine. Percentage of households using salt with sufficient iodine was higher in urban than in rural areas. The higher the quintiles of household expenditures the higher the percentage of households using salt with sufficient iodine. There was a trend that the higher the age the higher the percentage of low category of thyrotropin hormone level. Keywords: householdsalt, education, occupation, urban, rural, expenditure, thyrotropin hormone   ABSTRAK Garam beriodium merupakan strategi jangka panjang dan berkesinambungan untuk memperbaiki asupan iodium masyarakat. Sementara itu, kadar thyroid stimulating hormone (hormon tirotropin) dapat digunakan sebagai indikator kecukupan asupan iodium. Meneliti status sosial-ekonomi rumah-tangga yang menggunakan garam beriodium dan kadar hormon tirotropin di perkotaan.  Data yang digunakan untuk artikel ini adalah data Riskesdas 2007 yang mencakup 280.000 rumah-tangga. Data hormon tirotropin mencakup 9.457 individu umur 1 tahun keatas. Variabel yang digunakan untuk makalah ini meliputi klasifikasi desa, tes cepat pada garam, pendidikan dan pekerjaan kepala keluarga (KK), kadar hormon tirotropin. Sekitar 80 persen rumah-tangga,dimana KK tamat perguruan tinggi, menggunakan garam mengandung cukup iodium. Hanya 18 persen rumah-tangga yang KK-nya bekerja sebagai pegawai negeri menggunakan garam mengandung cukup iodium. Sekitar 70 persen rumah-tangga pada kuintil 5 pengeluaran rumah-tangga menggunakan garam mengandung cukup iodium. Sekitar 70 persen rumah-tangga di perkotaan menggunakan garam mengandung cukup iodium.Pada umur 1-4 tahun, persentase hormon tirotropin kategori rendah adalah 3,3 persen dan pada umur 60 tahun keatas adalah 15,8 persen.  Semakin tinggi tingkat pendidikan kepala rumah-tangga semakin tinggi persentase rumah-tangga yang menggunakan garam mengandung cukup iodium. Persentase rumah-tangga yang menggunakan garam mengandung cukup iodium adalah lebih tinggi di perkotaan dibandingkan di perdesaan.Semakin tinggi kuintil pengeluaran rumah-tangga semakin tinggi persentase rumah-tangga yang menggunakan garam mengandung cukup iodium. Ada kecenderungan semakin tinggi umur semakin tinggi persentase kadar tirotropin kategori rendah. [Penel Gizi Makan 2012, 35(2): 90-98] Kata kunci: garam rumah-tangga, pendidikan, pekerjaan, perkotaan, perdesaan, pengeluaran, hormon tirotropin